2014
DOI: 10.1177/0954406214525950
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of performance of bolt–nut connections, Part II: Experimental investigation

Abstract: In this work, bolt and nut geometries are modified for the improvement of fatigue life of the bolt–nut connections. The modifications are aimed at reducing the stress concentration at the thread roots by factors such as reducing the shank diameter, making axial hole in bolt, stepping the nut and their combinations. The effect of modifications is studied by experiment and simulation. The experimental results show that all types of modifications considered result in an improvement in the fatigue resistance of bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…However, finite element analysis demonstrates that the stress along the center axis of the bolt rapidly approaches a constant value at about one-quarter of the bolt diameter away from the bearing faces of the head and the nut. 18,19 Moreover, photoelasticity studies have shown that, at a distance of nearly of one-third of bolt diameter away from the bolt head, the nut, and the transition point, the stress approaches uniformity throughout the cross section. 20 Although for the measurement of clamping force using bolt elongation it is desirable that the FBG sensor be strategically placed in the region of uniform axial strain, it is not mandatory if proper FBG sensor calibration is performed.…”
Section: Theory Of Fbg Sensor Operationmentioning
confidence: 99%
“…However, finite element analysis demonstrates that the stress along the center axis of the bolt rapidly approaches a constant value at about one-quarter of the bolt diameter away from the bearing faces of the head and the nut. 18,19 Moreover, photoelasticity studies have shown that, at a distance of nearly of one-third of bolt diameter away from the bolt head, the nut, and the transition point, the stress approaches uniformity throughout the cross section. 20 Although for the measurement of clamping force using bolt elongation it is desirable that the FBG sensor be strategically placed in the region of uniform axial strain, it is not mandatory if proper FBG sensor calibration is performed.…”
Section: Theory Of Fbg Sensor Operationmentioning
confidence: 99%
“…16,17 Dragoni 18 studied the thread pitch effect on steel bolts fatigue strength. The fatigue limit slightly increases as the pitch decreases in small low-grade steel bolts.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have performed numerical simulations and experiments on joint shape changes aiming at reducing the stress concentration in fillets and at increasing the joints performance. 16,17 Dragoni 18 studied the thread pitch effect on steel bolts fatigue strength. The fatigue limit slightly increases as the pitch decreases in small low-grade steel bolts.…”
Section: Introductionmentioning
confidence: 99%
“…The former concerns the bolts' preload planning considering elastic interaction, including bolts number, distribution, preload sequence, preload size, etc. 6,7 In contrast, the latter mainly pays close attention to material creep, such as the bolt stress relaxation. 8 Due to elastic interaction, the tightened bolt loses part of its load as a result of the tightening of another bolt, which lies inside the influence area.…”
Section: Introductionmentioning
confidence: 99%